Network service chaining by using mashups technology in NFV (2017)
Network Service Chaining (NSC) is introduced by Network Function Virtualization (NFV) to give the possibility to select Network Services (NSs) according to the needs or requests of a user. Currently, there are problems that reduce the exibility of NSC and cause delays, tra c with unnecessary routes and few control options for administrators. Although there are di erent types of NSC (e.g. dynamic, and static) and some solutions (e.g. automatic algorithms, and frameworks) that allow choosing the one that suits the best the needs of the user, they do not give a full solution to the existing problem. In this undergraduate work, we propose an architecture for semi-automatic NSC, using advantages of mashups technology to achieve a solution to the current lack of exibility of the NSC. With proof-of-concept based on Software De ned Networks (SDN), we were able to demonstrate that our architecture allows solutions of low consumption in response time (<350 ms) and bandwidth (<3 KB), giving full control to the administrator to choose the network services that are executed and avoiding the need to have advanced knowledge.